2020
DOI: 10.3928/00220124-20200812-04
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Learning During COVID-19: A Teaching Strategy for Protected Code Blues

Abstract: In light of the COVID-19 pandemic and uncertainties around risk of transmission, urgent hospital resuscitation (also known as “Code Blue”) efforts are needed, pivoting to protect health care workers. This article provides teaching tips for “Protected Code Blues.” [ J Contin Educ Nurs . 2020;51(9):399–401.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Although cost-effective, a whiteboard is limited to visual communication and requires team members to keep looking at the board to read the written messages while performing time-sensitive procedures. Cheruku et al [6] used hospital-based mobile phones and networked videoconferencing, whereas Silver et al [7] used baby monitors. The 3 studies indicated the success of these communication strategies.…”
Section: Principal Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although cost-effective, a whiteboard is limited to visual communication and requires team members to keep looking at the board to read the written messages while performing time-sensitive procedures. Cheruku et al [6] used hospital-based mobile phones and networked videoconferencing, whereas Silver et al [7] used baby monitors. The 3 studies indicated the success of these communication strategies.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In light of these challenges, the American Heart Association (AHA), in collaboration with other professional societies, has recommended modifications to the standard CPR algorithms [1] and issued a COVID-19-related Interim Resuscitation Guideline (thereafter referred to as the AHA COVID-19 Resuscitation Guideline) [2]. Studies that applied the AHA COVID-19 Resuscitation Guideline and similar European guidelines are scarce [3][4][5][6][7]. In response to these gaps, our simulation-based study aimed to develop and test a protocol based on the AHA COVID-19 Resuscitation Guideline for adult patients in hospital settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these challenges, the American Heart Association (AHA), in collaboration with other professional societies, has recommended modifications to the standard CPR algorithms [1] and issued a COVID-19-related Interim Resuscitation Guideline (thereafter referred to as the AHA COVID-19 Resuscitation Guideline) [2]. Studies that applied the AHA COVID-19 Resuscitation Guideline and similar European guidelines are scarce [3][4][5][6][7]. In response to these gaps, our simulation-based study aimed to develop and test a protocol based on the AHA COVID-19 Resuscitation Guideline for adult patients in hospital settings.…”
Section: Introductionmentioning
confidence: 99%